Predator odour does not influence trappability of southern brown bandicoots (Isoodon obesulus) and common brushtail possums (Trichosurus vulpecula) - Mella, V.; Cooper, Christine; Davies, Stephen (CSIRO Publishing, 2010)
Predators cause changes in the behaviour of many prey species. This study investigated whether trappability of wild southern brown bandicoots (Isoodon obesulus) and common brushtail possums (Trichosurus vulpecula) was influenced by odour cues suggesting the presence of potential predators. Trapping success was compared between traps with predator scents and controls in two different experiments. The first measured trapping success of single clean traps, traps with unfamiliar herbivore (horse) odour and traps scented with predator (fox, cat, quoll and dingo) odours, while the second offered three choices (fox, dingo and clean traps) simultaneously. Frequency of capture of bandicoots and possums was not influenced by odour, mass or sex in either experiment. The lack of avoidance response observed in this study suggests that neither southern brown bandicoots nor common brushtail possums alter foraging behaviour in response to olfactory cues that suggest the presence of exotic or Australian predators. This is consistent with previous studies, which indicate that native Australian marsupials do not avoid predator odours.